2018
DOI: 10.21815/jde.018.099
|View full text |Cite
|
Sign up to set email alerts
|

Application of OSCE for Stage Assessment in Standardized Training for Oral Residents

Abstract: The aim of this study was to establish and implement an objective structured clinical examination (OSCE) for stage assessment in standardized training for oral residents, evaluating its validity and suitability. An OSCE was established for stage assessment of 158 residents in a program in Jiangsu Province, China. Its validity and suitability were evaluated using indices such as reliability and discrimination coefficients of assessment results. The established OSCE had eight stations: interpretation of auxiliar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…In recent years, the majority of studies have shown that the OSCE has many advantages in assessing the competence of practitioners, the clinical skills of medical students, and the expertise of specialists [16]. In addition, OSCE, as a method of objective assessment of students' abilities has great exibility and can be operated according to the characteristics of different disciplines and objective conditions under the basic framework [17]. The evaluation of students' comprehensive ability has always been the focus of medical educators at home and abroad.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the majority of studies have shown that the OSCE has many advantages in assessing the competence of practitioners, the clinical skills of medical students, and the expertise of specialists [16]. In addition, OSCE, as a method of objective assessment of students' abilities has great exibility and can be operated according to the characteristics of different disciplines and objective conditions under the basic framework [17]. The evaluation of students' comprehensive ability has always been the focus of medical educators at home and abroad.…”
Section: Discussionmentioning
confidence: 99%
“…The trainees in the 1st year accounted for the most number of the trainees whose emphasis degree and test scores increased after the outbreak. This result was due to the training objectives of Stage 1 ( 31 ). By contrast, the freshman trainees had less stress in terms of graduation and employment than seniors.…”
Section: Discussionmentioning
confidence: 98%
“…In relation to the quantity of stations, the Jordanian student considered the 67 stations a very high number 14 , differently from the students of this study, who judged the 6 station to be appropriate. Another study, considered 8 stations a good number with credible assessment results, and indices such as mean and discrimination coefficient of test scores from each station appropriated 4 . Therefore, the proposed protocol was found to be reliable and suitable.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the traditional methods, OSCEs (Objective Structured Clinical Examination) is a method for assessment of clinical competences 4 . The OSCE was introduced by Harden in 1975 5,6 and has attained international popularity in medical and health care education 7,8 .…”
Section: Introductionmentioning
confidence: 99%